2014
DOI: 10.1074/jbc.m113.536706
|View full text |Cite
|
Sign up to set email alerts
|

Defective Craniofacial Development and Brain Function in a Mouse Model for Depletion of Intracellular Inositol Synthesis

Abstract: Background: Lithium exerts a mood-stabilizing effect and inhibits myo-inositol monophosphatase (IMPase). Results: IMPase mutant mice had impaired jaw formation and mimicked lithium-induced behaviors. Conclusion: Craniofacial development and brain function require intracellular inositol production. Significance: This mouse model reveals molecular mechanisms relevant to understanding lithium's efficacy and inositolmediated developmental processes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 57 publications
1
21
0
Order By: Relevance
“…Berry et al 18 demonstrated in mice that homozygous deletion of the sodium myo-inositol cotransporter-1 (SMIT), whose product is responsible for importing inositol into cells, caused lethality of mice shortly after birth. Ohnishi et al 19 screened an ethyl-nitrosourea mutant library for Impa1 −/− mutations and found a Thr95Lys missense mutation, which caused perinatal death of the mice and was also rescued by inositol supplementation. Homozygotes exhibited hyperlocomotive behavior and prolonged circadian periods.…”
Section: Discussionmentioning
confidence: 98%
“…Berry et al 18 demonstrated in mice that homozygous deletion of the sodium myo-inositol cotransporter-1 (SMIT), whose product is responsible for importing inositol into cells, caused lethality of mice shortly after birth. Ohnishi et al 19 screened an ethyl-nitrosourea mutant library for Impa1 −/− mutations and found a Thr95Lys missense mutation, which caused perinatal death of the mice and was also rescued by inositol supplementation. Homozygotes exhibited hyperlocomotive behavior and prolonged circadian periods.…”
Section: Discussionmentioning
confidence: 98%
“…In addition, p53 induced INPP1 and INPP5 (28) that are involved in myo-inositol salvage pathway. Myo-inositol is one of the chemical compounds which is essential for living organisms (29), and myo-inositol depletion affects cell survival and growth (30). Myo-inositol was also reported to suppress tumor growth in vitro and in vivo (31)(32)(33)(34)(35)(36)(37)(38).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, higher levels of brain inositol are reported in bipolar disorder patients, and lithium reduces brain inositol levels in both patients and animals (Allison and Stewart, ; Davanzo et al, ). Also, IMPase knockout mice (specifically mice lacking IMPA1 that encodes the IMPase gene that regulates inositol metabolism in brain) show lithium‐like effects in behavioural models (Cryns et al, ; Ohnishi et al, ).…”
Section: Introductionmentioning
confidence: 99%